Flash hacks - Bhangal, Sham (O'Reilly, 2004)
"Covering the latest versions of the Flash authoring tool (Flash MX 2004 and Flash MX Professional 2004) and ActionScript 2.0, Flash Hacks pushes the envelope of what is possible in both motion graphics and ActionScript coding. Exploring the techniques and ideas in this book will expand your Flash horizons, helping you to make your designs more original and your applications more effective."--Jacket.